Efektivitas berpikir kritis peserta didik pada model guided inquiry learning dan model problem based learning - Sari, Fitri Niken; Sukidin, Sukidin; Tiara, Tiara (Jurnal Pendidikan Ekonomi (JUPE), 2025)
This study aims to determine the effectiveness of guided inquiry learning models and problem-based learning models on critical thinking skills of class X students at SMAN 2 Bondowoso. The type of research used is a quasi-experimental study with a non-equivalent control group design. Sampling using purposive sampling in class X B as the experimental class and class X C as the control class. Data collection techniques are observation, tests, and documents. Data analysis techniques are Independent Sample T-test and N-Gain test. The results of the study indicate that there is an effect of guided inquiry learning models on students' critical thinking skills with a significance value of 0.000 <0.05 and the N-Gain test in the experimental class of 0.3352 and the control class of 0.0390. From this comparison, it is concluded that the experimental class has a higher increase in critical thinking skills than the control class. Based on the N-Gain assessment criteria, the control class is included in the low criteria, namely N-Gain <0.30, while the experimental class is included in the medium category with a value of 0.30 ≤ N-Gain 0.70. This shows that the use of guided inquiry learning models has a significant influence on students' critical thinking skills.